2021
DOI: 10.1088/1757-899x/1200/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial Testing on Geogrid-reinforced Granular Soils

Abstract: Laboratory triaxial compression tests were carried out to investigate the mechanical behavior of dense sand and geogrid-reinforced granular soils. The tested sand having its mean particle size (D50) equal to 0.6 mm was adopted. Three geogrids with different longitudinal and transverse nominal strengths were used. The dimensions of the cylindrical soil specimen were 70 mm (diameter) × 160 mm (height). The relative density was equal to 70% for all tests. The reinforced sand specimens with one or two geogrid laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This phenomenon was more obvious in fine-grained sands. Similar laboratory studies and results regarding the performance of reinforced sands in triaxial shear apparatus have been reported by Moghaddas and Asakereh (2007), Khaniki and Daliri (2012), Mindiastiwi et al (2021), Skuodis et al (2020), and Yi and Du (2020) [5,6,8,17,18].…”
Section: A Review Of the Literaturesupporting
confidence: 84%
See 3 more Smart Citations
“…This phenomenon was more obvious in fine-grained sands. Similar laboratory studies and results regarding the performance of reinforced sands in triaxial shear apparatus have been reported by Moghaddas and Asakereh (2007), Khaniki and Daliri (2012), Mindiastiwi et al (2021), Skuodis et al (2020), and Yi and Du (2020) [5,6,8,17,18].…”
Section: A Review Of the Literaturesupporting
confidence: 84%
“…Given the higher growth rate of cohesion in the reinforcer with an aperture dimension of 5 mm and a thickness of 2 mm compared to the one with an aperture dimension of 3 mm and a thickness of 1 mm, we observe the positive effect of the tensile strength of the reinforcer on the cohesion growth, as reported by Mindiastiwi et al 2021; Yi, F. and Du, C., 2020; Skuodis et al 2020. They have concluded that the increasing peak shear strength is more pronounced with a higher number of geogrid and the geogrid with higher stiffness [8].…”
Section: Influence Of the Reinforcer Dimension Ratio On The Cohesion ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained showed that the geogrid creates apparent cohesion and a small change in the angle of internal friction [32]. The effect of the geogrid is better reflected through the reinforcement effect, which is expressed as the ratio of the maximum deviatoric stress with the geogrid to the maximum deviatoric stress without the geogrid [33]. Obtained results depend on the type of soil, the type of geogrid, and the confining pressure at which the tests were carried out [34].…”
Section: Introductionmentioning
confidence: 97%